Automated reasoning : 8th International Joint Conference, IJCAR 2016, Coimbra, Portugal, June 27-July 2, 2016, Proceedings /: 8th International Joint Conference, IJCAR 2016, Coimbra, Portugal, June 27-July 2, 2016, Proceedings. (2016) - Unknown
No abstract available